1999
DOI: 10.1086/315090
|View full text |Cite
|
Sign up to set email alerts
|

Human Interleukin‐12 Enhances Interferon‐γ–Producing Influenza‐Specific Memory CD8+Cytotoxic T Lymphocytes

Abstract: Interferon (IFN)-gamma synthesis of CD45RO+ (memory) and CD45RA+ (naive) CD8+ cytotoxic T lymphocytes (CTLs) and the role of interleukin (IL)-12 in the regulation of human CTL functions in virus-specific immunity were investigated. After culture with influenza virus, CD45RO+ CD8+ T cells from human peripheral blood mononuclear cells increased in frequency and exhibited significant major histocompatibility complex class I-mediated CTL activity, whereas CD45RA+ CD8+ T cells did not. Influenza virus-stimulated CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…We showed previously that IL-12 enhanced influenza virusspecific memory CD8 + CTL activity in humans 24,55 and recently that IL-12 with or without IL-18 augmented CTL responses in aged mice. 57,68 Other studies have demonstrated the ability of IL-12 to inhibit apoptosis and increase T cell functions.…”
Section: Effects Of Ril-12 Treatment On Ctl Responses Apoptosis and mentioning
confidence: 90%
See 1 more Smart Citation
“…We showed previously that IL-12 enhanced influenza virusspecific memory CD8 + CTL activity in humans 24,55 and recently that IL-12 with or without IL-18 augmented CTL responses in aged mice. 57,68 Other studies have demonstrated the ability of IL-12 to inhibit apoptosis and increase T cell functions.…”
Section: Effects Of Ril-12 Treatment On Ctl Responses Apoptosis and mentioning
confidence: 90%
“…First strand cDNA reverse transcription and cDNA amplification using gene specific primers were performed as previously described. 55,57 b-Actin was used as a positive control. The sense and anti-sense primer sequences used, respectively, were as follows: mb-actin, 5'-GTG GGC CGC TCT AGG CAC CAA-3' and 5'-CTC TTT GAT GTC ACG CAC GAT TTC-3'; mTNF-a: 5'-TTCTGTCTACTGAACTTCGGGGTGATCGGTCC-3' and 5' -GTAT-GAGATAGCAAATCGGCTGACGGTGTGGG-3'; mTNFRII (TNFRp75): 5'-GCAAGCACAGATGCAGTCTG-3' and 5'-GGTCAGAGCTGC-TACAGACG-3'.…”
Section: Elisa For Ifn-g and Tnf-amentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMC) were obtained and cryopreserved as described previously (11). Viruses used in CMI assays were A/Taiwan/1/86 (H1N1), B/Panama/45/90 and the three vaccine strains.…”
Section: Assaysmentioning
confidence: 99%
“…Cytotoxicity-Assays for cytotoxic lymphocytes (CTLs) were conducted as described previously (11,12). Briefly, cryopreserved PBMCs were thawed, washed and verified as >95% viable.…”
Section: Assaysmentioning
confidence: 99%
See 1 more Smart Citation